Development of National Digital Evidence Metadata - Bambang Sugiantoro (Department of Informatics, UIN Sunan Gunung Djati Bandung, 2019)
The industrial era 4.0 has caused tremendous disruption in many sectors of life. The rapid development of information and communication technology has made the global industrial world undergo a revolution. The act of cyber-crime in Indonesia that utilizes computer equipment, mobile phones are increasingly increasing. The information in a file whose contents are explained about files is called metadata. The evidence items for cyber cases are divided into two types, namely physical evidence, and digital evidence. Physical evidence and digital evidence have different characteristics, the concept will very likely cause problems when applied to digital evidence. The management of national digital evidence that is associated with continued metadata is mostly carried out by researchers. Considering the importance of national digital evidence management solutions in the cyber-crime investigation process the research focused on identifying and modeling correlations with the digital image metadata security approach. Correlation analysis reads metadata characteristics, namely document files, sounds and digital evidence correlation analysis using standard file maker parameters, size, file type and time combined with digital image metadata. nationally designed the highest level of security is needed. Security-enhancing solutions can be encrypted against digital image metadata (EXIF). Read EXIF Metadata in the original digital image based on the EXIF 2.3 Standard ID Tag, then encrypt and insert it into the last line. The description process will return EXIF decryption results in the header image. This can secure EXIF Metadata information without changing the image quality